Intelligent and Integrated IoT-based Energy Management System (I3EMS) for Beauty Bishop - Dr. I. Priya Stella Mary (International Journal of Advanced Science and Technology, 2020)
One of the widespread applications of Internet of Things (IoT) is the smart office solution. Smart office technology facilitates to control electrical appliances either automatically or with the use of one single device such as the Smartphone, Amazon Echo, Alexa device and Thermostat etc. Incumbents can even control the appliances while sitting at their offices or from any other places in the world. Smart Office Technology has become an indispensable part of IoT (Internet of Things). In this paper, an Intelligent and Integrated IoT-based Energy Management System (I3EMS) is proposed to lessen power consumption in Bishop Heber College (BHC) offices efficiently. This cost effective proposed system decreases the consumption of electricity and the electrical devices can be controlled either automatically or through a mobile app. The proposed system facilitates to achieve sustainable development goals